Comparación de pronósticos de la estructura temporal de tasas de interés de México para distintas especificaciones del modelo afín - Alejandra Lelo-de-Larrea (Banco de México, 2020)
– Four specifications of an affine model with risk aversion and no arbitrage conditions are estimated for the Mexican Term Structure of Interest Rates, contrasting their empirical properties and the accuracy of their in and out of sample forecasts. The traditional models are extended by adding macroeconomic variables to analyze if the latter provide sufficient information to improve the adjustment and the forecast of interest rates. Using monthly data of the Zero Coupon Bonds, VIX, WTI, exchange rate, inflation and growth in the period 2002-2017, it is found that, although there is no superiority of a single model for the in and/or out of sample forecast of the yield curve, adding macroeconomic variables helps to improve the short and medium term forecasts independently of the type of factors used.
Keywords: C12; C32; C53; E43; E47; G12; 330; Afin Model; Yield Curve Forecast; Principal Components; Kalman Filter; No-Arbitrage Condition